(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article examines the topical task of modern banking institution management—the formation of effective strategic development models. It substantiates the importance of ensuring the long-term sustainability of the banking business in the context of increasing competition, digitalization, climate change, and global economic shocks, especially for Ukrainian banks operating in conditions of economic instability and military threats. The purpose of the article. The study aims to develop theoretical and methodological foundations and practical recommendations for the formation of strategic development models for a banking institution that will ensure its adaptation to changes in the external environment and increase competitiveness and sustainability in the context of global economic and technological transformations. Methods. To achieve the set goal, several tasks were identified, including describing the primary goal of strategic bank management, characterizing the essence and defining the tasks of the banking business development management Strategy, establishing the features of the formation of strategic development models of a banking institution and the key principles of developing an appropriate Strategy; reflecting the interaction scheme of individual aspects of the bank’s development Strategy formation and determining the impact of external and internal factors on this process. Results. The paper describes the primary goal of strategic bank management, characterizes the essence and defines the tasks of the banking business development management Strategy. The features of forming strategic development models of a banking institution and the key principles of developing a banking business development management Strategy are established. The paper reflects the interaction scheme of individual aspects of the bank’s development Strategy formation. It determines the impact of external and internal factors on the formation of strategic development models of a banking institution. Conclusions. The study emphasizes the need to form flexible and adaptive strategic development models for banking institutions capable of responding to dynamic changes in the external environment, ensuring their competitiveness, sustainability, and innovation.